Cryptocurrencies Transit to a Carbon Neutral Environment: From Fintech to Greentech Through Clean Energy and Eco-Efficiency Policies - Dimitrios Koemtzopoulos; Georgia Zournatzidou; Konstantina Ragazou; Nikolaos Sariannidis (Energies)
Fintech prioritizes the progression of issues related to environmental conservation and the consequences of climate change. This study is among the first investigations exploring the relationship between fintech and sustainable energy. It presents potential financial models that might be developed to assist companies in remaining operational via the use of renewable and clean energy sources. We employ a bibliometric analysis as the statistical methodology to address the study topic. We extract bibliometric data from the Scopus database employing the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) approach, thereafter analyzing the data with the R statistical programming language and the bibliometric applications Biblioshiny and VOSviewer. The results of the research indicate that fintech companies are committed to achieving carbon neutrality and investing in strategies such as environmental, social, and corporate governance (ESG) which may help them reduce their carbon footprint and enhance their eco-efficiency. In contrast to the United Kingdom, which is frequently regarded as the world’s preeminent financial center, Chinese fintech enterprises appear to demonstrate a more fervent dedication to the improvement of their ecological transition. However, the results, ultimately, emphasize the transition of fintech to an alternative paradigm, namely greentech. Greentech is a new fintech-dependent paradigm which will help cryptocurrencies and fintech reduce their environmental impact and promote carbon-neutral financial institutions via investment. Greentech aims to decarbonize the financial industry by investing in renewable resources and clean energy, therefore enhancing the sector’s environmental sustainability.